Experimental study of the macrobenthic colonisation and secondary production in the artificial reefs of Algarve coast - Moura, Ana Cristina Barroso (2012)
Tese de dout., Ciências do Mar, Faculdade de Ciências do Mar e do Ambiente, Universidade do Algarve, 2010